The Law Of Defamation In The New Millenium - Trindade, F.A. (Journal of Malaysian and Comparative Law, 2019)
The law of defamation is intended to protect reputations. The reputations of individuals (including politicians), the reputations of business corporations and until recently even the reputations of the public authorities such as local councils.